Looking at the Centre-Province Relationship via “Sedd” Maintenance Processes: Local Administration and the State Centre in Eighteenth - Century Ottoman Egypt - Mücahide Nihal Engel (Türkiyat Mecmuası)
As the archive records of the period show, the imperial government did not hesitate to invest in Egypt, one of its most profitable provinces. Divan-ı Hümayun, Egyptian villagers and local administrators were always in close contact with regard to the management of the environmental factors in favour of production, both to ensure the continuation of commercial activities and to sustain agricultural production. Ottoman archives in Istanbul present a wide range of defter series and edict records related to Ottoman Egypt in the 18th century, which is known as the century of ‘ayan’ in the Ottoman history studies. In these records, the main agenda topics on the management of environmental factors revolve around the repair works of existing walls to protect agricultural areas from sea water, the preservation of irrigation canals, and the protection of cisterns and canals that provide drinking water to the public. The villagers' expertise on the Nile and the local geography guided the repair processes, while they were financed by the state treasury. In Alexandria and the surrounding villages, the priority of the reaya and local administrators was to show the necessary care within the framework of sustainability by working together so that these walls, called sedd, would not collapse and not become in need of repair. However, in the second half of the 18th century, as the local elements did not fulfill their duties, the area to be repaired increased and the state treasury suffered a loss. In 1768, we see that the state centre raised this issue, asking the local elements to carry out their duties as before. However, the state centre’s warning the local elements and desire to rectify the situation coincide with Bulutkapan Ali Bey's uprising. Nevertheless, the following attempts such as the intervention of Gazi Hasan Pasha in 1786 failed in the long term too. Shedding light on the centre-province relations in the second half of the eighteenth century, this article focuses on the communication of the state with the local elements regarding the preservation of agricultural lands in Alexandria. It also reveals the agricultural production environment of Alexandria with archival documents.